An Unpreconditioned Boundary-Integral for Iterative Solution of Scattering Problems with Non-Constant Leontovitch Impedance Boundary Conditions (Communications in Computational Physics, 2014)
This paper concerns the electromagnetic scattering by arbitrary shaped threedimensional imperfectly conducting objects modeled with non-constant Leontovitchimpedance boundary condition. It has two objectives. Firstly, the intrinsically well-conditioned integral equation (noted GCSIE) proposed in [30] is described focusingon its discretization. Secondly, we highlight the potential of this method by comparison with two other methods, the first being a two currents formulation in whichthe impedance condition is implicitly imposed and whose the convergence is quasi-optimal for Lipschitz polyhedron, the second being a CFIE-like formulation [14]. Inparticular, we prove that the new approach is less costly in term of CPU time andgives a more accurate solution than that obtained from the CFIE formulation. Finally,as expected, it is demonstrated that no preconditioner is needed for this formulation.